2014
DOI: 10.1186/1471-2393-14-287
|View full text |Cite
|
Sign up to set email alerts
|

Timing and factors associated with first antenatal care booking among pregnant mothers in Gondar Town; North West Ethiopia

Abstract: BackgroundAntenatal care service which is among strategies to maintain maternal and fetal wellbeing is strongly recommended to be initiated early during pregnancy. To developing world where there is uncommon practice of pre-pregnancy care and support, timely commencement is crucial in getting potential benefits from some of the elements of the care. Therefore, we sought to assess timing and factors associated with the first antenatal care booking among pregnant mothers attending antenatal care clinics in Gonda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
81
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(123 citation statements)
references
References 9 publications
24
81
10
Order By: Relevance
“…It can be inferred that the increase in ANC visits with increase in age could be attributed to the fact that better health education is given to pregnant mothers during antenatal care sessions. The finding is consistent with the study of O'Meara et al [45], Gudayu et al [46], and Rai et al [37] that household size of a pregnant mother significantly influences her ANC use.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…It can be inferred that the increase in ANC visits with increase in age could be attributed to the fact that better health education is given to pregnant mothers during antenatal care sessions. The finding is consistent with the study of O'Meara et al [45], Gudayu et al [46], and Rai et al [37] that household size of a pregnant mother significantly influences her ANC use.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…The timing of first booking ranged from first month after last menstrual period to ninth month of gestation. The proportion of women who came for their first ANC within recommended time is lower than studies done in Gondar, Addis Ababa, and higher than studies conducted in Hadiya, Kembata zone, Yem special district, and EDHS 2011 [4,13,[18][19][20][21]. Possible explanation for this might be those who have more proportion of early ANC due to better access and awareness regarding services while the lower proportion may be due to time variation in this study and the access and awareness improvement.…”
Section: Discussioncontrasting
confidence: 59%
“…According to the result, mothers of age ≤ 25 years were found to be more likely to have early initiation of ANC when compared with others (COR = 1.309 95% CI 0.92, 2.458), but not significant. This idea was slightly supported by study done in Addis Ababa, Yem, Gondar, and Debrebrhan; this idea contradicts the study done in Tanzania (18)(19)(20)(21)8). This might be because younger mothers were more informed and convincible to seek appropriate prenatal care.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A study done in Ethiopia also reported almost similar result (17.7 weeks). 27 However, a previous study conducted in Myanmar reported much lower gestational age at first ANC (15 weeks) while those detected in Ethiopian and Tanzanian studies were more than 20 weeks. 14,18,24 These discrepancies may be due to differences in time or site of study or differences in education and/or socioeconomic status among study population.…”
Section: Discussionmentioning
confidence: 85%